Facile and scalable design of light-emitting and ROS-generating hybrid materials made of polyurea gels embedding a molybdenum cluster-based salt. Issue 25 (9th June 2021) - de Jesus, Natana A. M.; de Oliveira, Ricardo; Amela-Cortes, Maria; Dumait, Noée; Cordier, Stéphane; Molard, Yann; Molina, Eduardo F.
Abstract : Singlet oxygen production evidenced upon irradiation in the UV-A region widens hybrid polyurea materials' potential in the field of photodynamic therapy. Abstract : Here, we demonstrate a facile and scalable preparation via sol–gel chemistry of hybrid polyurea gels containing various amounts of a phosphorescent inorganic octahedral molybdenum cluster-based ternary salt, namely Cs2 Mo6 Br14 . The influence of the Cs2 Mo6 Br14 content (1–10 wt%) on the polyurea matrix and its physical properties are studied in depth by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and X-ray fluorescence microanalysis (μ-XRF). Regardless of the amount of cluster loaded into the polyurea, the integrity of these species was preserved and their dispersion is homogeneous as shown by μ-XRF mapping. Spectroscopic-structural analyses reveal a significant increase of the chain mobility (glass transition temperature T g ) from −65 °C to −55 °C after the incorporation of Cs2 Mo6 Br14 (DSC analyses). The FTIR studies show that the homogeneity of the dispersion is ensured by supramolecular interactions between the ether-type oxygen atoms of the PEO chains and the cluster compound. Photoluminescence studies show that the metal cluster emission properties are well retained within the host matrix whatever the loaded content. Such a combination of materials demonstrates the feasibility to fabricate a rubber NIR-emitting device. Moreover, the loaded polyurea is also able to produce reactive oxygen species (ROS) upon irradiation in the UV-A region, opening new perspectives as versatile membranes in the field of photodynamic therapy.